A Spatio-Temporal Analysis of Sex-Ratio in Districts of Jammu and Kashmir, India - Javaid Ahmad Andrabi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
In the present an attempt has been made to analyze the sex ratio in districts of Jammu and Kashmir and is based on decennial census report. Sex-ratio is one of the most fundamental demographic and social attribute to measure prevailing equality between males and females in the society. According to Census 2011, the national average of sex ratio was 943 while it was only 889 Jammu and Kashmir, which was much lower than the national average, as a result of patriarchal society, religious belief, traditions and customs and also aided with modern medical technology. Jammu and Kashmir State along with Gujarat and Bihar experienced low sex ratio in 2011 in comparison to 2001 census. The sex ratio in Jammu and Kashmir has always remained unfavorable in spite of various social, educational, economic and cultural developments in the society. In addition in India   Kannur district in Kerala state has highest sex ratio of 1133 females per 1000 males has also a Ladakh district in Jammu & Kashmir state has lowest sex ratio of 583 females per 1000 male. The present study shows  many ups and downs in sex ratio over a period of time in 1901 to 2011.The declining sex ratio is an indicator of low status of female and unequal roles assigned to females, which is one of the grave concern and demographic threats for the state.